IN SILICO SCREENING OF PHYTOCHEMICAL CONSTITUENTS FROM DESMODIUM GYRANS DC. AS GLYCOGEN SYNTHASE KINASE-3β (GSK-3β) - S. GOPALAKRISHNAN; R. RAJAMEENA; R. SUBRAMANIAN (International Journal of Pharma and Bio Sciences, 2015)
In the present study the phytochemical constituents isolated from the ethanol extract of the leaves of Desmodium gyrans DC by GC-MS analysis, were subjected to molecular docking studies for the inhibition of glycogen synthase kinase-3β (GSK-3β) protein, a main target for wound healing activity by Wnt signaling pathway. The comparative docking of the isolated phytochemicals and standard drug Nitrofurazone to glycogen synthase kinase-3β has been performed. The activation domain of GSK-3β consisted of Pro 136, Val 135, Asp 200. The activation domain of GSK-3β docked with the phytochemical constituents, ethaverine, mataven, 1,2-Amino-4-(2,4-dichlorophenyl)7-methyl-5-oxo-4H,5H-pyrano(4,3b) pyran-3-carbonitrile, sumatriptan, 1-Methyl-7-(4-nitrophenyl)[1,3] oxazolo [2,3f] purine 2,4(1H,3H)dione, 2-Methylamino-1-phenyl propanone showed the docking scoring of -110.16, -99.48, -90.15, -87.21, -78.48, -61.92 Kcal.mol-1 respectively. The standard showed the docking score of -64.06 Kcal.mol-1 with good affinity toward active pocked. The results revealed that ethaverine is considered as a good inhibitor of GSK-3β.